2022
DOI: 10.1038/s41419-022-04902-w
|View full text |Cite
|
Sign up to set email alerts
|

miR-188-3p targets skeletal endothelium coupling of angiogenesis and osteogenesis during ageing

Abstract: A specific bone capillary subtype, namely type H vessels, with high expression of CD31 and endomucin, was shown to couple angiogenesis and osteogenesis recently. The number of type H vessels in bone tissue declines with age, and the underlying mechanism for this reduction is unclear. Here, we report that microRNA-188-3p (miR-188-3p) involves this process. miRNA-188-3p expression is upregulated in skeletal endothelium and negatively regulates the formation of type H vessels during ageing. Mice with depletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…| 11 of 18 WANG et al (Srinivasan et al, 2022), miR-188-3p (He et al, 2022), and miR-21 (Xiong et al, 2021) have been implicated in the regulation of the aging process. Collectively, these studies highlight the critical regulatory role of non-coding RNA molecules, represented by miR-7, in the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…| 11 of 18 WANG et al (Srinivasan et al, 2022), miR-188-3p (He et al, 2022), and miR-21 (Xiong et al, 2021) have been implicated in the regulation of the aging process. Collectively, these studies highlight the critical regulatory role of non-coding RNA molecules, represented by miR-7, in the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…Fractured bones were dissected at various time intervals and fixed for 24 hours with 4% paraformaldehyde, following scanned and analyzed with high-resolution micro-computed tomography (μCT) (Skyscan 1172, Bruker MicroCT, Kontich, Belgium) as previous reported 54 , 55 . The callus index (CI) of fractured bone was evaluated by calculating the ratio of the maximal diameter of the callus to the diameter of the adjacent diaphysis.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining was conducted as previously described 54 , 55 . Briefly, femora were treated for antigen retrieval by digestion with 0.05% trypsin at 37 °C for 15 minutes, and stained with primary antibodies, including anti-Ctsk (ab19027, 1:200, Abcam), anti-GFP (ab6673, 1:200, Abcam), and anti-Ocn (M137, 1:500, Takara) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…They suggested that miRNA-188-3p directly targets integrin b3 in endothelial cells, inhibiting type H vessel formation and contributing to age-related type H vessel decline. By contrast, knocking out miRNA-188 can alleviate the type H vessel decline in aged mice (46).…”
Section: Integrinsmentioning
confidence: 96%
“…For endothelial cells, adhesion to ECM via cell-surface integrins is necessary for endothelial cell proliferation and angiogenesis (45). Previous studies showed that integrins, such as integrin b1 and integrin b3, also exist in type H endothelial cells and play a crucial role in angiogenesis (46). He and colleagues found specific overexpression of miRNA-188-3p in the senescent endothelial cells of type H vessels, which inhibits the type H vessel formation, especially in aged mice.…”
Section: Integrinsmentioning
confidence: 98%